Community empowerment in rural infrastructure development program - Waridin Waridin; Atika Dzulkhijiana; Izza Mafruhah (Economic Journal of Emerging Markets, 2018)
This study evaluates the role of stakeholders in the Rural Infrastructure Develop-ment Program (RIDP) and analyzes the intensity of community participation in the program implementation with a willingness to pay. Also, it analyzes the factors that influence community empowerment. This research uses sequential mixed method with descriptive statistics, Context Input-Output and Outcome Process (CIPOO), Analytical Hierarchy Process (AHP) and Willingness to Pay (WTP). The results of the analysis show that the main actors in the community empowerment program are the community followed by the local government, academician, and business actors. The community WTP is IDR 5,100, which helps them to maintain sustainability and maintain projects built by the government actively. The empowerment process is the most important factor followed by context and input as the second priority, while output and outcome become the third priority.